2018
DOI: 10.1007/s13364-018-0400-2
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial positioning of individuals in a group of feral horses: a case study using drone technology

Abstract: Special thanks are due to Viana do Castelo city for supporting our project. We are also grateful to Agostinho Costinha, the director of Descubra Minho, Lourenço Almada of Associação O Caminho do Garrano. We also thank the villagers in Montaria for their support during our stay, Tetsuro Matsuzawa for the generous guidance throughout the study, and Dora Biro and Valéria Romano for helpful comments on an earlier version of our manuscript. The study was financially supported by grants from the Japan Society for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 57 publications
2
53
0
Order By: Relevance
“…When correcting for kinship in the present study, a positive correlation between proximity and mutual grooming was found. This discovery corroborates a previous report stating that proximity is correlated with mutual grooming between pairs of horses in the Serra d'Arga Mountain of Portugal [54].…”
Section: Mutual Grooming and Affiliative Relationships Between Horsessupporting
confidence: 92%
See 1 more Smart Citation
“…When correcting for kinship in the present study, a positive correlation between proximity and mutual grooming was found. This discovery corroborates a previous report stating that proximity is correlated with mutual grooming between pairs of horses in the Serra d'Arga Mountain of Portugal [54].…”
Section: Mutual Grooming and Affiliative Relationships Between Horsessupporting
confidence: 92%
“…The aforementioned hypotheses must be tested on multiple herds and in longer-term observations of Misaki and other feral horses worldwide and can be extrapolated to understand behavioral stereotypies in horses in intensive production systems. The findings of this study suggest that comparisons between horses and other taxa, such as primates, may effectively elucidate the mechanisms by which interactions between group members maintain and strengthen their social relationships [15,54,57].…”
Section: Discussionmentioning
confidence: 90%
“…Secondly, the nearest neighbour tended to be located to the right front of a target individual more frequently than to the left front, although this trend was not significant. Thirdly, the nearest neighbour was less frequently located behind a target individual, which is consistent with a previous study (Inoue et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…there was 30 min between two consecutive still images). The distortion of the camera lens was corrected using the lens filter function in Photoshop CC (Adobe Systems incorporated) (Inoue et al, ). The drone took off 10–50 m away from the horses.…”
Section: Methodsmentioning
confidence: 99%
“…Highly coordinated collective motion is a cornerstone of many biological systems at all scales, from cell colonies [1,2] to insect swarms [3][4][5][6], fish schools [7,8], bird flocks [9][10][11], ungulate herds [12][13][14], and even human crowds [15,16]. Moving together in large groups and using social information can provide numerous benefits, including enhanced predator avoidance [17][18][19], more efficient resource exploitation [20,21], energy savings [22][23][24] and efficient learning of migration routes [25,26].…”
Section: Introductionmentioning
confidence: 99%